Effect of Premature Tube Extrusion for Simple Congenital Nasolacrimal Duct Obstruction: A Comparison of Monocanalicular and Bicanalicular Intubation. Issue 1 (January 2022) - Dryden, Stephen C.; Meador, Andrew G.; Awh, Caroline; Smith, Barbara D.; Eder, Adrianna E.; Bohn, Shiva N.; Hoehn, Mary E.; Fowler, Brian; Fleming, James C.
Abstract : Abstract: The objective of this article is to compare the incidence of premature dislocation of silicone tubes and the effect on treatment success between monocanalicular (MCI) and bicanalicular (BCI) intubation in pediatric patients with simple congenital nasolacrimal duct obstruction. Retrospective comparative case series of 108 eyes of 78 pediatric patients with simple congenital nasolacrimal duct obstruction who underwent probing with either BCI (n = 38 eyes) or MCI (n = 70 eyes) from 2017 to 2020. Premature tube extrusion was defined as any tube removed prior to the 3 month postoperative appointment. Success was defined as resolution of tearing 3 months post tube removal. Ages ranged from 10 months to 5.35 years (mean, 1.95 years; Standard deviation (SD), 0.91). Premature tube extrusion occurred in 15 eyes with BCI and 29 eyes with MCI. Success rates were not significantly different regardless of intubation type between the planned tube removal (90.6%) and the premature tube extrusion cohorts (84.1%), P  = 0.89. There was no significant difference in treatment success between the planned tube removal (92.7% MCI, 87% BCI) and the premature tube extrusion cohorts (86.2% MCI, 80% BCI). Complications included 2 infections (1 MCI, 1 BCI) and 2 cases of tube related keratopathy (1 MCI, 1 BCI) that all resolved with tube removal. There were 2 BCI patients that presented to the emergency department for premature tube extrusion. Silicone intubation regardless of stent type is an effective treatment for simple congenital nasolacrimal duct obstruction. There was no significant difference in treatment success between tubes that extrude prematurely, and tubes removed at term based on type of intubation. Abstract : Supplemental Digital Content is available in the text